Existence, uniqueness, and quasilinearization results for nonlinear differential equations arising in viscoelastic fluid flow - F. Talay Akyildiz; K. Vajravelu (Differential Equations and Nonlinear Mechanics)
Solutions for a class of nonlinear second-order differential equations arising in steady Poiseuille flow of an Oldroyd six-constant model are obtained using the quasilinearization technique. Existence, uniqueness, and analyticity results are established using Schauder theory. Numerical results are presented graphically and salient features of the solutions are discussed.